An Overview on Atomization and Its Drug Delivery and Biomedical Applications - Anu Mohandas (Applied Sciences, 2021)
Atomization is an intricate operation involving unstable and complex networks with rupture and fusion of liquid molecules. There are diverse details that typify the spray formation, which are the technique and configuration of the atomization process, dimension and structure of the nozzle, experimental parameters, etc. Ultimately, the process generates fine sprays from the bulk of a liquid. Some examples of atomization that we come across in our day-to-day life are antiperspirant or hair spray, shower head, garden sprinkler, or cologne mist. In this review paper we are briefly discussing the theoretical steps taking place in an atomization technique. The instabilities of the jet and sheet are explained to understand the underlying theory that breaks the jet or sheet into droplets. Different types of atomization processes based on the energy sources are also summarized to give an idea about the advantages and disadvantages of these techniques. We are also discussing the various biomedical applications of the electrohydrodynamic atomization and its potential to use as a drug delivery system. In short, this paper is trying to demonstrate the diverse applications of atomization to show its potency as a user friendly and cost-effective technique for various purposes.